PERAN MA’HAD AL-ZAYTUN DALAM IMPLEMENTASI LAGU INDONESIA RAYA MENURUT UNDANG-UNDANG NOMOR 20 TAHUN 2003 DAN MAQASHID SYARIAH - Haritsah, Haritsah; Ngainnur Rohmah, Siti; Rahim, Abdur (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
Currently, numerous issues related to morality, values, and character among the younger generation are prevalent in society. This phenomenon is caused by the decline in noble national values and the erosion of nationalism and patriotism within the community. The Indonesian national anthem, "Indonesia Raya," is one means of shaping a country's national identity and serves as an expression of nationalism and patriotism. This study aims to examine the role of Ma’had Al-Zaytun in implementing the "Indonesia Raya" anthem according to Law No. 20 of 2003 and the principles of Maqashid Syariah. This research employs a literature study with a juridical-normative legal approach. Primary data sources include Law No. 20 of 2003 and the book Maqashid Syariah: Concepts, Principles, and Applications in Social Life by Fadil Salim, while secondary data sources comprise books, journals, documents, and regulations. The study discusses the role of Ma’had Al-Zaytun in implementing the "Indonesia Raya" anthem in accordance with the National Education Law No. 20 of 2003 and the principles of Maqashid Syariah. The anthem is sung daily by the Ma’had Al-Zaytun community to instill a love for the country, national pride, and unity. Additionally, on national holidays, Ma’had Al-Zaytun invites interfaith leaders to share insights on social, educational, and cultural issues to contribute to national progress. This implementation aligns with Maqashid Syariah, as Ma’had Al-Zaytun emphasizes the preservation of students' intellect and soul through a healthy lifestyle, counseling, prayer, reflection, and cognitive learning, which includes critical thinking skills and technology use in education. These initiatives aim to maintain the physical, mental, and intellectual well-being of students and develop productive and meaningful character, in accordance with Islamic teachings and national values embedded in the "Indonesia Raya" anthem. Keywords: Ma’had Al-Zaytun; Indonesia Raya; Maqashid Syariah; Law No. 20 of 2003